2021
DOI: 10.1097/scs.0000000000008249
|View full text |Cite
|
Sign up to set email alerts
|

Resurfacing of Face and Neck Using Superthin Thoracodorsal Artery Perforator Free Flaps

Abstract: Background: Resurfacing of facial and neck defects is challenging due to the unique skin color, texture, and thickness of the region. With the development of microsurgical reconstruction, perforatorfree flaps can provide adequate soft tissue. However, despite various modifications, such flaps hardly satisfy cosmetic requirements, due to differences in color and bulkiness. We have used superthin thoracodorsal artery perforator (TDAp) free flaps to overcome these limitations. Methods: Between January 2012 and Ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Of the strategies used to manage patients with CR, Z-plasty had the highest success rate at 62.5%. As new strategies for managing postburn neck contracture with flap reconstructions emerge, [15][16][17] larger studies that can inform best practices to prevent CR are needed. When following patients postoperatively, on average, CR (256.4 ± 249.4 days) presented later than initial contracture (128.9 ± 84.9 days).…”
Section: Discussionmentioning
confidence: 99%
“…Of the strategies used to manage patients with CR, Z-plasty had the highest success rate at 62.5%. As new strategies for managing postburn neck contracture with flap reconstructions emerge, [15][16][17] larger studies that can inform best practices to prevent CR are needed. When following patients postoperatively, on average, CR (256.4 ± 249.4 days) presented later than initial contracture (128.9 ± 84.9 days).…”
Section: Discussionmentioning
confidence: 99%
“…Superthinning methods have been implemented in conventional thin flaps to impressively reduce the subcutaneous fat layers. Studies have reported ranges of 1.5–6 mm of thickness for superthin SCIP flaps (Kim et al, 2015; Lee et al, 2017), 3–5 mm for superthin TDAP flaps (Chang et al, 2022; Hattori et al, 2020), and 3–6 mm for superthin ALT flaps (Suh et al, 2022; Xie et al, 2016). This technique may lead to subdermal plexus injury, leading to flap compromise despite the high level of dexterity the authors performed (Lee et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The second misconception is that lateral thoracic region tissue is much bulkier than thigh and inguinal tissue. Based on our experience and knowledge about vessel and perforator anatomy and fat distribution, dissection and defatting skills, we have already harvested thin and super‐thin flaps from the lateral thoracic region (Chang et al, 2022; Kim et al, 2017; Kim, Youn, et al, 2016). Also compared to the proximal thoracic area, once we choose distal perforators during flap harvest, we can harvest thin flaps and perform very short intramuscular dissection due to the thin distal LD muscle.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, the Metzenbaum scissors are used to push and pressure the superficial fat layer of the flap from the margin so that the bulging fat can be easily and safely cut. This process which is named "pushing with pressure and cutting" can continue until the superficial fat tissue is all removed except around the perforator (Chang et al, 2022).…”
Section: Casementioning
confidence: 99%